Effects of three acepromazine doses on the incidence of morphine-induced vomiting, sedation and some physiological variables in dogs - Monteiro, Eduardo Raposo (2017)
Background: Acepromazine was found to reduce the incidence of vomiting induced by opioids such as morphine, hydromorphone and oxymorphone in dogs. Despite the effectiveness of the phenothiazine in preventing opioid-induced vomiting in this species, a single dose of acepromazine (0.05 mg/kg) was tested and the influence of dose on the antiemetic effect of the drug is unknown. The primary objective of this study was to evaluate the effect of three acepromazine doses on the incidence of vomiting induced by morphine in dogs. A secondary aim was to assess the degree of sedation and effects on physiological variables following administration of the combinations tested. Materials, Methods & Results: All dogs received 0.5 mg/kg morphine (IM). Fifteen min before morphine, dogs in the Control, ACPLD, ACPMD and ACPHD groups were administered (IM) physiological saline or acepromazine at doses of 0.025, 0.05 and 0.1 mg/kg, respectively. In Phase 1, purpose-bred dogs (n = 8) underwent each of the four treatments in a randomized, crossover design; the incidence of vomiting, sedation, pulse rate (PR), systolic, mean and diastolic blood pressures (SAP, MAP and DAP) were investigated for 60 min. Sedation was assessed by a numeric descriptive scale (NDS, range 0-3) and a simple numerical scale (SNS, range 1-10). In Phase 2, client-owned dogs (n = 50) received a single treatment and only the incidence of vomiting was assessed. There was no significant difference between groups on the incidence of vomiting recorded in Phase 1, Phase 2 and the average of Phases 1 and 2. A significant decrease in PR was observed in most groups but no significant difference was detected between groups. Blood pressure decreased in all groups; during most of the evaluation period, SAP, MAP and DAP were significantly higher in the Control than in other treatments. Dogs in this study presented mild to intense sedation. A significant difference in NDS scores was observed between the Control and ACPMD groups whereas for SNS scores, significant differences were detected between the ACPMD and ACPHD groups compared with the Control group. The number of dogs presenting intense sedation as judged by the NDS (NDS score = 3) were: 1/8, 3/8, 3/8 and 4/8 dogs in the Control, ACPLD, ACPMD and ACPHD groups, respectively. Discussion: The hypothesis of the study was rejected. The acepromazine dose did not influence the frequency of morphineinduced vomiting, the degree of sedation or cardiovascular variables after administration of either treatment. The frequency of vomiting was high (≥ 75%) in dogs of the present study regardless of the treatment administered. There was no significant difference in the frequency of vomiting in ACPLD, ACPMD and ACPHD as compared to the Control group. This finding was unexpected because it has been reported in a previous study that acepromazine reduced the incidence of opioid-induced vomiting in dogs. ACPLD, ACPMD and ACPHD improved the quality of sedation compared to the Control treatment but no significant difference in sedation scores was observed among these groups. These findings suggest that, when combined to morphine, there is no improvement in sedation when the acepromazine dose is increased above 0.025 mg/kg in dogs.Despite a significant decrease, mean values of PR, SAP, MAP and DAP remained within the physiological range for conscious dogs. In summary, none of the acepromazine doses was effective in preventing morphine-induced vomiting in dogs. Sedation is greater after acepromazine-morphine combinations than after morphine alone and is not influenced by the acepromazine dose. Cardiovascular effects induced by combinations administered in this study were well tolerated and of little clinical relevance to healthy conscious dogs.